EXPLORING GEOPARK DESTINATION VALUE - Nafri, Intan Aryati; Lenggogeni, Sari (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2020)
Purpose- This research aims to analyze and explore the information of Geopark and its component which are cultural values, scenic values, environmental values, social valuesDesign/methodology/approach- In this study the authors used qualitative research which produces descriptive that directed to describe the phenomena that occur related to Geopark tourismFindings- this study gave a conclusion about the new value created in the geopark, they are emotional value and financial value which differs from the concept of the. Scenic value, Environmental value, Cultural value, Social value are the same as the concept in reference journal of this research. Implications- the result shows that indicating that values can still be generalized while Environmental values are the most considered by tourists to visit GeoparkKeywords: geopark, cultural values, scenic values, environmental values, social values